Humanistic Approach in Foreign Language Teaching (Teachers’ Perspectives) - Milošević, Olja R. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Language learning is a cognitively demanding task which requires a positive emotional attitude on the part of the learner. Humanistic approaches to foreign language teaching provide a good framework for incorporating both cognitive and affective components in language teaching. It is argued that the recognition of the importance of student affective reactions in the area of foreign language teaching is essential for successful language acquisition. This paper consists of two parts. The first introductory part reviews literature and provides the theoretical background of humanistic approaches in language teaching. The second part of the paper presents findings from a small scale qualitative research that was carried out with foreign language teachers from three different educational institutions in Serbia. The aims of this research were to establish to what extent teachers understand the importance of humanistic approaches and how teachers contribute to the quality of interaction in the classroom. In order to understand teachers’ perspectives, the in-depth interviews were carried out with teachers. A semi structured format of the interviews helped to determine teachers’ views on the learning process and the key components in developing students’ communicative competence. The findings indicate that the teachers understand the importance of affective variables and the way they impact the learner’s readiness to engage in activities that will develop language proficiency. Humanistic approaches contribute to developing positive attitudes, establishing good relationships and thus increase language competency.